Trust among peers as a social character of job design, and its relationship with internal work motivation and job performance among academics in the International Islamic University Malaysia (IIUM) - Brahim, Bouzidani (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2011)
This study investigated trust among peers as a social characteristic of job design, and its relationship with two work-related variables; internal work motivation as an attitudinal outcome of job design; and job performance as a behavioural outcome of job design. The participants were selected by employing systematic random sampling. Out of 841 academic members in the seven Kulliyyahs of the International Islamic University Malaysia, Gombak campus, a total of 132 subjects (N = 132) were systematically selected to participate in this study. Using structural equation modelling the results demonstrated that trust among peers has a significant relationship with job performance, whereas a non-significant relationship was found with internal work motivation. For the two components of trust among peers, it was found that the affective component was not significantly related to either of the two outcomes variables; however, the cognitive component was found to have a significant relationship with job performance.